“Ma santé est mauvaise actüellement…“ An Enlightener and His Health. Part One: Relation to Health and Illness Using the Example of Wenzel Anton of Kaunitz-Rietberg and His Relatives (Theatrum historiae, 2020)
The study refers to an unexplored aspect of the well-known personality of Count and later Prince Wenzel Anton of Kaunitz-Rietberg (1711–1794). The first part of the two-part paper presents his relation to the healthy and sick body, diseases that tormented him, and it also describes how he perceived various illnesses that troubled not only him but also his relatives and friends. Attention is paid especially to the question of whether and how diseases affected Kaunitz and his environment, what impacts they had on him, where he sought help and whether certain periods of his life can be considered essential in this sense. The studied sources are viewed through the optics of Patientengeschichte.
Keywords: aristocracy; early modern period; 18th century; Patientengeschichte; health and illness; Wenzel Anton of Kaunitz-Rietberg